Altered distribution of adrenergic constrictor responses contributes to skeletal muscle perfusion abnormalities in metabolic syndrome. (February 2017) - Lemaster, Kent; Jackson, Dwayne; Welsh, Donald G.; Brooks, Steven D.; Chantler, Paul D.; Frisbee, Jefferson C.
Abstract: Purpose: Although studies suggest elevated adrenergic activity paralleling metabolic syndrome in OZRs, the moderate hypertension and modest impact on organ perfusion question the multi‐scale validity of these data. Methods: To understand how adrenergic function contributes to vascular reactivity in OZR, we utilized a multi‐scale approach to investigate pressure responses, skeletal muscle blood flow, and vascular reactivity following adrenergic challenge. Results: For OZR, adrenergic challenge resulted in increased pressor responses vs LZRs, mediated via α1 receptors, with minimal contribution by either ROS or NO bioavailability. In situ gastrocnemius muscle of OZR exhibited blunted functional hyperemia, partially restored with α1 inhibition, although improved muscle performance and VO2 required combined treatment with TEMPOL. Within OZR in situ cremaster muscle, proximal arterioles exhibited a more heterogeneous constriction to adrenergic challenge, biased toward hyperresponsiveness, vs LZR. This increasingly heterogeneous pattern was mirrored in ex vivo arterioles, mediated via α1 receptors, with roles for ROS and NO bioavailability evident in hyperresponsive vessels only. Conclusions: These results support the central role of the α1 adrenoreceptor for augmented pressor responses and elevations in vascular resistance, but identify an increased heterogeneity of constrictor reactivity in OZR that is presently of unclear purpose.